2021
DOI: 10.1111/jopr.13371
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Surgical Guide Fixation and Implant Location on Accuracy of Static Computer‐Assisted Implant Surgery

Abstract: Purpose: To evaluate the accuracy of static computer-assisted implant surgery (sCAIS) for tooth-supported free-end dental implantation with the aid/and without the aid of fixation pins to secure the surgical template through comparison between planned, 3D printed guide position and placement implant position. Materials and Methods: Thirty-two duplicated maxillary resin models were used in the present in vitro study. Digital planning was performed and fabrication of a surgical template that allowed implant plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 29 publications
1
16
0
1
Order By: Relevance
“…One of the most effective ways to reduce the mobility of the templates is to provide rigid support at the far free end (Al-Omiri et al, 2017), including fixation pins (Chen et al, 2023;Pessoa et al, 2022;Raico et al, 2017), bone support spot (Lin et al, 2020), and anchor microscrew-cap system (Mai & Lee, 2020). Chen Xi et al found that the group without fix pin generated the Angle deviation (3.65 ± 1.39°), 3D deviation at crest (1.58 ± 0.55 mm), and 3D deviation at apex (2.18 ± 0.79 mm), whereas the group with bilateral fixation pins on the buccal and palatal sides significantly reduced the Angle deviation to 1.88 ± 0.86°, 3D deviation at crest to 1.09 ± 0.51 mm and 3D deviation at apex to 1.53 ± 0.45 mm (Chen et al, 2023;Raico et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the most effective ways to reduce the mobility of the templates is to provide rigid support at the far free end (Al-Omiri et al, 2017), including fixation pins (Chen et al, 2023;Pessoa et al, 2022;Raico et al, 2017), bone support spot (Lin et al, 2020), and anchor microscrew-cap system (Mai & Lee, 2020). Chen Xi et al found that the group without fix pin generated the Angle deviation (3.65 ± 1.39°), 3D deviation at crest (1.58 ± 0.55 mm), and 3D deviation at apex (2.18 ± 0.79 mm), whereas the group with bilateral fixation pins on the buccal and palatal sides significantly reduced the Angle deviation to 1.88 ± 0.86°, 3D deviation at crest to 1.09 ± 0.51 mm and 3D deviation at apex to 1.53 ± 0.45 mm (Chen et al, 2023;Raico et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…When the surgical guide is not supported firmly enough, the transmitted force could result in positional deviation or dislodgement of the surgical guides (Lee et al., 2016; Seo & Juodzbalys, 2018). One of the most effective ways to reduce the mobility of the templates is to provide rigid support at the far free end (Al‐Omiri et al., 2017), including fixation pins (Chen et al., 2023; Pessoa et al., 2022; Raico et al., 2017), bone support spot (Lin et al., 2020), and anchor microscrew‐cap system (Mai & Lee, 2020). Chen Xi et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Implants in distal extension gaps resulted in more significant deviation when compared to implants placed in posterior areas with adjacent bilateral teeth support due to possible intraoperative guide movement, tilting, and bending, particularly in long cantilever lengths. Although the mismatch between the planned and final achieved positions can be measured, no information on the source of inaccuracy can be assessed (38). Most of our patients belonged to the group of long posterior extension gaps prone to bending and tilting of the static guide.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding other factors that influence template accuracy, Zhou et al (Zhou et al, 2018) conducted a comprehensive comparison of various clinical factors and concluded that guide accuracy may be affected by guide position (maxilla or mandible), guide fixation (fixation screw or not) (Pessoa et al, 2022), type of guide (total or partial) (Mangano et al, 2018;Lou et al, 2021;Fotopoulos et al, 2022;Gargallo-Albiol et al, 2022), flap approach (open flap or flapless), differences in implant system (Zhu et al, 2021), high temperature sterilization (Marei et al, 2019;Kirschner et al, 2022) and support mode (tooth-supported, mucosa-supported or mixed-supported) (Pan et al, 2022). In addition, Henprasert et al concluded that there was no significant difference in accuracy between 3D-printed and milled guides, but found that the former had the advantages of high efficiency and reduced material waste (Henprasert et al, 2020).…”
Section: Research Status On Additive Manufacturing Applications In Im...mentioning
confidence: 99%